Mahalnya Pendidikan di Perguruan Tinggi Berdasarkan Perspektif Hukum Islam dan Solusi Al-Quran - Misnawati Misnawati; Any Noegroho; Sumiati Sumiati; Anwarsani Anwarsani; Nabila Salwa; Levi Alkausar (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2024)
Education is a basic right of every individual and has a crucial role in the development of human resources. However, the cost of higher education is often an obstacle for many families, especially in developing countries like Indonesia. This research examines the high cost of higher education from an Islamic legal perspective, highlighting how the Koran offers a solution to this problem. A qualitative approach with literature studies is used to understand the views of Islamic law and Al-Quran solutions regarding higher education costs. The Koran teaches the importance of education and offers mechanisms such as zakat, sadaqah, and waqf to support more just and equitable education. This research shows that the implementation of Islamic principles can help overcome barriers to access to higher education, promote social justice, and build quality human resources